1992
DOI: 10.1007/bf00195329
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytoplasmic inorganic phosphate in light-induced activation of H+-pumps in the plasma membrane and tonoplast of Chara corallina

Abstract: A unique variant strain of Chara corallina, which contains little inorganic phosphate in the vacuole ([Pi]v) was isolated. The level of cytoplasmic inorganic phosphate ([Pi]c) in these cells was the same as that in normal cells. Using these unique cells, we studied the change in [Pi]c and the effect of Pi on the activities of electrogenic H(+)-pumps associated with the plasma membrane and tonoplast. Upon illumination, the plasma membrane of C. corallina became hyperpolarized by 15 mV, the pH of the vacuolar sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…However, the activation mechanism of the H 1 -ATPase by photosynthetic electron transport in the fern remains unclear. The photosynthesis-induced membrane hyperpolarization by H 1 -ATPase has been reported in green algae Chara (Takeshige et al, 1992) and in aquatic angiosperm Vallisneria leaves (Harada et al, 2002). In Vallisneria, the H 1 -ATPase is activated by a decrease in the K m for ATP through photosynthetic active radiation and is suppressed by DCMU.…”
Section: Guard Cell Chloroplasts Mediate Stomatal Opening In Adiantummentioning
confidence: 97%
“…However, the activation mechanism of the H 1 -ATPase by photosynthetic electron transport in the fern remains unclear. The photosynthesis-induced membrane hyperpolarization by H 1 -ATPase has been reported in green algae Chara (Takeshige et al, 1992) and in aquatic angiosperm Vallisneria leaves (Harada et al, 2002). In Vallisneria, the H 1 -ATPase is activated by a decrease in the K m for ATP through photosynthetic active radiation and is suppressed by DCMU.…”
Section: Guard Cell Chloroplasts Mediate Stomatal Opening In Adiantummentioning
confidence: 97%
“…Because Takeshige et al (1992) reported a lightdependent decrease in the cytoplasmic content of Pi in the internodal cells of Chara corallina, and Sicher and Kremer (1988) reported a similar decrease in the leaves of Hordeum vulgare, a light-dependent retrieval of PM H + -ATPase activity through the C-terminal autoinhibitory domain might occur in V. gigantea. However, in the case of Chara corallina (Takeshige et al 1992), the light-induced membrane hyperpolarization was observed much earlier than the detectable decrease in the cytoplasmic level of Pi. On the other hand, in the samples prepared from the V. gigantea leaves before and after in vivo illumination, we determined the kinetic parameters of the activities of ATP hydrolysis and H + transport in the absence of Pi (Harada et al, in press).…”
Section: Presence Of Multiple Isoforms Of Pm H + -Atpasementioning
confidence: 95%
“…These results indicate that, in the presence of Pi, the light-dependent changes in the K m may occur at higher concentration ranges of ATP. Consequently, although the cytoplasmic concentration of ATP in plant cells supposedly ranges from submillimolar to a few millimolar (Keifer and Spanswick 1979;Kikuyama et al 1979), a photosynthesis-dependent decrease in the K m for ATP might accelerate the activity of the PM H + -ATPase, because the PM H + -ATPase is supposed to be constitutively exposed to cytoplasmic Pi in vivo at approximately 10-15 mM (Takeshige et al 1992). Separately, the level of ATP in a very limited space contiguous to the PM, which should have critical effects on the activity of the PM H + -ATPase ), remains to be determined.…”
Section: Presence Of Multiple Isoforms Of Pm H + -Atpasementioning
confidence: 96%
See 2 more Smart Citations